The synergistic effect of the atherogenic index of plasma and hyperuricemia on the prediction of coronary chronic total occlusion lesion: an observational cross-sectional study - Han, HongYa; Liu, XiaoLi; Zhao, Qi; Wang, ZhiJian; Sun, Yan; Ma, Xiaoteng; Li, MengChen; Ma, HanYing; Liu, YuYang; Shi, DongMei; Cheng, YuJing; Zhou, YuJie (Frontiers in Cardiovascular Medicine, 2024)
Background The atherogenic index of plasma (AIP) and hyperuricemia (HUA) have been shown to be closely associated with morbidity and mortality of coronary artery disease. However, studies targeting predictive value of AIP and HUA for chronic total occlusion (CTO) lesions are still lacking. Methods In total, 5,238 patients meeting the eligibility criteria were recruited in this analysis. CTO was defined as the condition of lesions without forward blood flow and with over three months of occlusion time. AIP was calculated as log10 [triglycerides (mmol/L)/high-density lipoprotein cholesterol (mmol/L)]. HUA was defined based on sex-specific criteria: serum uric acid 420 and 360 μmol/L for males and females, respectively. Results CTO lesions were presented in 907 (17.3%) patients. Compared with patients showing lower AIP levels and non-HUA, the CTO lesion risks increased by 5.225 and 2.765 times in patients with higher AIP levels and HUA. Patients with AIP >0.15 and HUA exhibited the greatest CTO incidence (odds ratio 11.491; 95% confidence interval 9.019–14.641, P < 0.001). In addition, AIP combined with HUA had significantly increased effects (a 38.5% increase in CTO risk) relative to the sum of respective effects. Conclusion Patients having higher AIP levels and HUA exhibited the highest CTO incidence, in comparison with patients who have the increased single index. AIP combined with HUA displayed significant synergistic effect on the prediction of CTO lesion.